KINERJA PELAYANAN TERPADU SATU PINTU DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA PALEMBANG - Rizki Pratiwi; Heru Nurasa; Wike Anggraini (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2020)
This study aims to describe the performance of one-stop integrated services at Invesment and One Stop Service (DPMPTSP) in Palembang City, South Sumatra, and to identify the factors that cause decreased the performance, and explore more about the efforts to improve employee performance. The research method used in this research is qualitative research with descriptive methods and inductive approaches. Data collection techniques are observation, interview and documentation. The results showed that the performance of the Palembang City Investment Service and One Stop Integrated Service was good. Despite the downgrade due to several factors such as budget constraints, changes in staff structure, increased competition between provinces and the unavailability of public service malls. However, DPMPTSP Palembang City can make several efforts to improve its performance so that it can regain the predicate that was previously achieved.